First detection of gamma-ray sources at TeV energies with the first imaging air Cherenkov telescope of the TAIGA installation. (December 2020) - Postnikov, E B; Astapov, I I; Bezyazeekov, P A; Blank, M; Borodin, A N; Bruckner, M; Budnev, N M; Bulan, A V; Chiavassa, A; Dyachok, A N; Gafarov, A R; Garmash, A Yu; et al.
Abstract: TAIGA array addresses gamma-ray astronomy at energies from a few TeV to several PeV as well as cosmic ray physics from 100 TeV to several EeV. A 1 km 2 TAIGA setup will consist of 120 wide-angle detectors of the Cherenkov timing array TAIGA-HiSCORE and three imaging air Cherenkov telescopes with the field of view diameter of 9.6°. In this paper, first experimental results of the first operation stage are presented: signal detection from two gamma-ray sources, the Crab Nebula and Markarian 421, by the first IACT in stand-alone mode. The detected signal is shown to be in agreement with the Monte Carlo expectation. In future, gamma-ray signal will be detected by a larger number of TAIGA telescopes as well as the TAIGA-HiSCORE array, that is, in combined operation mode.